Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1038/mi.2015.85
|View full text |Cite
|
Sign up to set email alerts
|

Bone marrow transplantation alters lung antigen-presenting cells to promote TH17 response and the development of pneumonitis and fibrosis following gammaherpesvirus infection

Abstract: Hematopoietic stem cell transplantation (HSCT) efficacy is limited by numerous pulmonary complications. We developed a model of syngeneic bone marrow transplant (BMT) followed by infection with murine gamma herpesvirus (γHV-68) that results in pneumonitis and fibrosis and mimics human “non-infectious” HSCT complications. BMT mice experience increased early lytic replication, but establish viral latency by 21 days post infection (dpi). CD4 T cells in BMT mice are skewed towards IL-17A rather than IFN-γ producti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
70
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(75 citation statements)
references
References 50 publications
1
70
0
Order By: Relevance
“…It is possible that IL-17 responses arising in the gut may further impact lung disease (114). IL-17 is involved in the elimination of certain pathogens (115) and is implicated in the pathogenesis of several pulmonary pathologies including asthma, Sarcoidosis, Obliterative Bronchiolitis, CF and bone marrow transplant related pneumonitis(116120). …”
Section: The Microbiome Shapes Immunitymentioning
confidence: 99%
See 1 more Smart Citation
“…It is possible that IL-17 responses arising in the gut may further impact lung disease (114). IL-17 is involved in the elimination of certain pathogens (115) and is implicated in the pathogenesis of several pulmonary pathologies including asthma, Sarcoidosis, Obliterative Bronchiolitis, CF and bone marrow transplant related pneumonitis(116120). …”
Section: The Microbiome Shapes Immunitymentioning
confidence: 99%
“…The neutralization of IL-17 in mice harboring microbiota led to dampened inflammation and reduced disease burden (121). Several studies have implicated IL-17 in hepatic fibrosis, and certain experimental models of pulmonary fibrosis are IL-17A dependent (120, 122, 123). Furthermore, studies examining the development of intestinal fibrosis have reported an association with alterations in the microbiota and Th17 responses (124).…”
Section: The Microbiome Shapes Immunitymentioning
confidence: 99%
“…Single cell suspension was prepared from the lungs of C57BL/6 mice three days post infection of murine gamma herpesvirus 68 (MHV-68) intranasal at a dose of 5 × 10 4 pfu/mouse (Zhou, et al 2016). CD11c + cells were then enriched by using anti-mouse CD11c microbeads.…”
Section: Discussionmentioning
confidence: 99%
“…We developed a protocol of isolating lung APCs from normal mice and then adoptively transferring them to syngeneic bone marrow transplanted mice. We used this protocol to determine whether normal lung APCs are sufficient to restore T helper cell polarization in response to herpesvirus infection post-transplant (Zhou et al ., 2016). …”
Section: Introductionmentioning
confidence: 99%
“…To study lung development or lung diseases in mouse models, the lungs can be removed from mice and either frozen and embedded in optimal cutting temperature (OCT) compound or chemically preserved and embedded in paraffin. To preserve lung tissue architecture, we filled the lung with 1 ml of OCT compound for preparing frozen sections, or 10% buffered formalin for paraffin sections (Zhou et al , 2016). Lung sections are then sliced from frozen or paraffin-embedded lungs and mounted onto slides for preparation of staining.…”
Section: Introductionmentioning
confidence: 99%